Antiatherogenic and Cardioprotective Effects of Black Chokeberry (Aronia melanocarpa) Juice in Aging Rats. (13th August 2015) - Daskalova, Elena; Delchev, Slavi; Peeva, Yulia; Vladimirova-Kitova, Lyudmila; Kratchanova, Maria; Kratchanov, Christo; Denev, Petko
Abstract : Age-related diseases are a social problem of global significance and their prevention by natural products is a research area of particular interest. The present study is an approach to counteract the risk factors for atherosclerosis arising in the aging process by supplementation of chokeberry juice. It employed a model of healthy adult rats monitored for a number of somatometric, serum lipidogram, and histopathological parameters, related to risk factors and their response to supplementation with antioxidant-rich chokeberry juice. The results were used to calculate different atherogenic and cardioprotective indices, and all results were compared to those of young healthy rats. Chokeberry juice proved an extremely rich source of polyphenols resulting in very high antioxidant activity. Treatment with Aronia juice significantly lowered the proatherogenic low-density lipoprotein fraction of the animals studied and led to a 16.5% decrease in their total cholesterol. Atherogenic indices in Aronia -supplemented animals clearly showed lower atherogenic risk and cardioprotective indices indicated protection of the cardiovascular system. Besides that, chokeberry juice retarded the age-related changes in the aortic wall and can be recommended as a prophylactic tool for healthy aging.